Social work practices and the ecological sustainability of socially vulnerable communities - Rocha, H. B. (Sustainability, 2018)
Environmental problems are also social problems. Social work, as a scientific area, has increasingly assumed the importance of including environmental problems in social intervention. This close linkage to ecological issues is particularly relevant when addressing vulnerable communities. In this article, we analyze the results of a study focused on social work intervention in two Portuguese eco-neighborhoods in the context of ongoing urban regeneration projects, which suggest that social vulnerability accentuates the damage of exposure to environmental threats and amplifies its effects. The analysis of data collected from social workers, through 9 semi-structured interviews and through questionnaires (N = 131), with the residents of the neighborhoods together with non-participant observation, allowed to highlight the difficulties, contradictions, but also the potential of this type intervention. Results appear to support an eco-social model which may help social worker to promote social transformation and change, respecting community rhythms, promoting empowerment of individuals, addressing the challenges of socially vulnerable communities within the complexity of a globalized world.